Effect of pimobendan on left atrial function in dogs with preclinical myxomatous mitral valve disease - Sarcinella, Fabio (Open Vet J, 2019)
BACKGROUND: Left atrial (LA) function is an important determinant of the left ventricular (LV) filling, playing a key role in maintaining optimal cardiac performance. Pimobendan is a phosphodiesterase III inhibitor with positive inotropic and vasodilator effects. The present study aims to investigate the effects of pimobendan on LA function in dogs with stage B2 myxomatous mitral valve disease (MMVD). AIM: The aim of this investigation was to study the effects of pimobendan on LA function in dogs with preclinical MMVD. METHODS: Twenty-seven dogs with stage B2 MMVD were retrospectively included. LA function was assessed before and 1–6 months following pimobendan initiation. For each dog, two-dimensional (2D) echocardiography was performed to assess LA diameter and volume for each phase of the LA cycle and to assess complete, passive, and active LA function. Pulsed-wave tissue Doppler imaging (TDI) of the left ventricular longitudinal myocardial velocity associated with atrial contraction (A’), both at the level of the interventricular septum and the LV free wall, was also used as an indicator of LA function. RESULTS: There were no significant differences in any of the left atrial variables pre- and posttreatment. CONCLUSION: Echocardiographic estimates of LA function by 2D diameters and volumes and TDI A’ in dogs with MMVD do not change after treatment with pimobendan.